Estimating Molecular Gas Content in Galaxies from Polycyclic Aromatic Hydrocarbon Emission - Lulu Zhang; Luis C. Ho (The Astrophysical Journal, 2023)
Emission from polycyclic aromatic hydrocarbons (PAHs), a commonly used indicator of star formation activity in galaxies, also has the potential to serve as an effective empirical tracer of molecular gas. We use a sample of 19 nearby galaxies with spatially resolved mid-infrared Spitzer spectroscopy, multiwavelength optical and mid-infrared imaging, and millimeter interferometric CO(1–0) maps to investigate the feasibility of using PAH emission as an empirical proxy to estimate molecular gas mass. PAH emission correlates strongly with CO emission on subkiloparsec scales over the diverse environments probed by our sample of star-forming galaxies and low-luminosity active galactic nuclei. The tight observed correlation, likely a consequence of photoelectronic heating of the diffuse interstellar gas by the PAHs, permits us to derive an empirical calibration to estimate molecular gas mass from the luminosity of PAH emission that has a total scatter of only ∼0.2–0.25 dex. Mid-infrared bands sensitive to PAH emission (e.g., the Spitzer/IRAC4 and WISE/W3 filters) can also be used as a highly effective substitute for this purpose.